STUDI LITERATUR FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL - Zakiah Zakiah; Isnaniah Isnaniah; Dwi Lestari (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2023)
Abstract According to data from the World Health Organization (WHO), the prevalence of anemia in pregnant women was 41.8% (WHO, 2010). The prevalence of anemia in pregnant women in Indonesia increased compared to 2013, in 2013 as many as 37.1% of pregnant women were anemic while in 2018 it increased to 48.9% (Riskesdas, 2018). The purpose of this study was to determine the factors associated with the incidence of anemia in pregnant women. This research method uses a literature study method taken from 10 articles, 3 international articles and 7 national articles. The analysis in this study uses thematic analysis. The results of the study of 10 articles, it was found that the incidence of anemia worth between 11.8% - 62%, age at risk worth between 24% - 71.8%, third trimester gestation age worth between 51% - 62.5%, risk parity worth between 6.1% - 57.7%, gestation interval <2 years worth between 5% - 53.5%, and malnutrition status worth between 31.4% - 58%. Of the 8 articles 6 articles 75% stated that there was a relationship between age and the incidence of anemia and 2 articles 25% stated that there was no relationship between age and the incidence of anemia, from 2 articles 100% that discussed gestational age stated that there was a relationship. gestational age with the incidence of anemia, of the 9 articles there were 5 articles 55.5% which stated that there was a relationship between parity and the incidence of anemia and 4 articles 44.5% which stated that there was no relationship between parity and the incidence of anemia, of 3 articles, there are 2 articles 66.6% which state that there is a relationship between pregnancy distance and the incidence of anemia and 1 article 33.4% states that there is no relationship between pregnancy interval and the incidence of anemia, from 4 articles 100% that discuss parity states that there is a relationship between parity and the incidence of anemia. There is a relationship between age, gestational age, parity, gestational distance and nutritional status with the incidence of anemia in pregnant women Keywords : Incidence of Anemia, Age, Gestational Age, Parity, Birth Distance, Nutritional Status Abstrak Menurut data World Health Organization (WHO) secara global prevalensi anemia pada ibu hamil adalah 41,8% (WHO, 2010). Prevalensi anemia pada ibu hamil di Indonesia meningkat dibandingkan dengan 2013, pada tahun 2013 sebanyak 37,1% ibu hamil anemia sedangkan pada tahun 2018 meningkat menjadi 48,9% (Riskesdas, 2018).Tujuan penelitian ini adalah untuk mengetahui Faktor-faktor yang Berhubungan dengan Kejadian Anemia pada Ibu Hamil. Metode penelitian ini menggunakan metode Studi Literatureyang diambil dari 10 artikel, 3 artikel internasional dan 7 artikel nasional. Analisis pada penelitian ini menggunakan analisis tematik. Hasil dari penelitian 10 artikel, didapatkan kejadian anemia bekisar antara 11,8 % - 62%, umur beresiko bekisar antara 24% - 71,8%, usia kehamilan Trimester III bekisar antara 51% - 62,5%, paritas beresiko bekisar antara 6,1% - 57,7%, jarak kehamilan < 2 tahun bekisar antara 5% - 53,5%, dan status gizi kurang bekisar antara 31,4% - 58%. Dari 8 artikel terdapat 6 artikel 75% menyatakan ada hubungan umur dengan kejadian anemia dan 2 artikel 25% menyatakan tidak ada hubungan umur dengan kejadian anemia, dari 2 artikel 100% yang membahas usia kehamilan menyatakan ada hubungan usia kehamilan dengan kejadian anemia, dari 9 artikel terdapat 5 artikel 55,5% yang menyatakan ada hubungan paritas dengan kejadian anemia dan 4 artikel 44,5% yang menyatakan tidak ada hubungan paritas dengan kejadian anemia, dari 3 artikel terdapat 2 artikel (66,6%) menyatakan ada hubungan jarak kehamilan dengan kejadian anemia dan 1 artikel 33,4% menyatakan tidak ada hubungan jarak kehamilan dengan kejadian anemia, dari 4 artikel 100% yang membahas paritas menyatakan ada hubungan paritas dengan kejadian anemia. Terdapat hubungan antara umur, usia kehamilan, paritas, jarak kehamilan dan status gizi dengan kejadian anemia pada ibu hamil. Kata Kunci : Kejadian Anemia, Umur, Usia Kehamilan, Paritas, Jarak Kelahiran, Status Gizi